Enhancing entrepreneurial skills of employees in the education process - Ristovsk Natasha; Suzana Stankovska (UTMS Journal of Economics, 2018)
Modern organizations need to have a built-in management system in function of monitoring the employees' potentials and outputs, and mechanisms that will influence their initiative for entrepreneurship. The purpose of this paper is to elaborate entrepreneurship in teaching, focusing on entrepreneurial learning, the characteristics of contemporary teachers, the innovation and creativity in teaching, and the role of management in educational institutions. The motivation and professional development of the staff in the educational institutions are analyzed as part of the modern management functions. It is highlighted that the creativity and innovation of the modern teacher unequivocally influences and encourages students' entrepreneurship spirit and behaviour. In this regard, the authors recommend that is necessary to have a national strategy for entrepreneurial learning, as well as institutional policies, measures and programs that enable designing appropriate organizational culture that will encourage, support and develop entrepreneurial skills among employees in the educational institutions in order to provide quality education in accordance with the world trends and standards. This paper is an action research conducted in order to prove the influence of the entrepreneurial skills of teachers in creating and applying modern methods of teaching for producing competitive labour force in accordance with the market needs.
Keywords: M10; M20; I20; 330; entrepreneurial skills; motivation; innovation; quality; education